Examining English Language Teachersa Beliefs in the Context of English Language Education Reforms (By Eba Mijena) (Global Journal of Human-Social Science, 2015)
This study was aimed to examine English language teachers' beliefs about the teaching and learning of English language in the context of English language education reforms in western Ethiopia. It made survey with 125 school teachers from 43 schools. Data were collected during the ELT Enhancement Workshop organized by Wollega University at three of its campuses in the months of February 2013, March 2013 and April 2014. The questionnaire focused on gathering data on teachers' current thinking using the Likert Scale. The data collected using questionnaire were analyzised using percentages. These data were substantiated with the data collected using interviews. The findings of the study have shown that in spite of the introduction of various teacher development programmes (like CPD, induction, ELIP and other related workshops), English language teachers have mixed beliefs about the use of language teaching approaches. The study, therefore, suggests that the pre-service and in service trainings which address teachers' beliefs need to be the focus area in the future professional development programmes for ELT teachers in the study area.
Keywords: beliefs; mixed belief; context; language education reforms; teacher development programmes